(untitled) - Mumford, Lewis (New York, 1951)
Contents: In these volumes i have sought to deal in a unified way with man's nature, his work, and his life-dramas, as revealed in the development of contemporary Western civilization.
Keywords: Triết học, Trung Quốc,Philosophy, Chinese